Daya Tarik Rasa Takut Pada Visualisasi Komunikasi Lingkungan - Lukki Lukitawati; Nur Indah Wuriani (UMSU, 2020)
This study conduct discourse analysis on air pollution impact visualization of Aku dan Polusi campaign images. Visualisation is a vital strategies on shaping public perception of a complex and distant environmental issue. Aku dan Polusi deployed a series of emotive photo, headline and caption to visualize scientific research of air pollution impact. This study analyzed four chosen campaign images using children as actors with fearful headlines from multimodal discourse analysis perspective. Specifically, this study described two discursive strategies being employed on the campaign,1)the use of fear appeals approach in visualizing the effects of air pollution and 2) the use of children as actors to evoke emotional reactions from the campaign target, namely parents, especially mothers. The findings of this study underlines potential exploitation of using vulnerable group in order to raise public awareness on an environmental issue. Represent the vulnerable group as the one who shouldered the burden of fixing environmental problem will exclude policy maker responsibility out of the text at the same time.